Celebrating marriage : the spiritual wedding of the believer - Jakes, T. D. (Tulsa, OK : Albury Pub., 2000)
"In this fifth study of Ephesians, T.D. Jakes explores the wonder of our marriage covenant with Jesus Christ. The more we grasp all that earthly marriage is intended to be, the better we understand this most intimate of relationships with the Lord."--Cover.
Our kinsman redeemer -- A new life of honor -- Sacrificial love -- Submission -- Giving your life -- As he loves himself -- Intimacy.
Includes bibliographical references (pages 123-124).
Keywords: Marriage -- Religious aspects -- Christianity; Bible. -- Criticism, interpretation, etc